2013
DOI: 10.1186/1475-2859-12-104
|View full text |Cite
|
Sign up to set email alerts
|

The Rhodococcus opacus TadD protein mediates triacylglycerol metabolism by regulating intracellular NAD(P)H pools

Abstract: BackgroundThe Gram-positive actinomycete Rhodococcus opacus is widely studied for its innate ability to store large amounts of carbon in the form of triacylglycerol (TAG). Several groups have demonstrated that R. opacus PD630 is capable of storing anywhere from 50 to 76% of its cell dry weight as TAG. While numerous studies have focused on phenomenological aspects of this process, few have sought to identify the underlying molecular and biochemical mechanisms responsible for the biosynthesis and storage of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In the last years, several genes/proteins and their contributions on TAG metabolism have been well described in R. opacus PD630 or R. jostii RHA1 used as models. Examples of these studies include proteins such as diacylglycerol acyltransferase enzymes (DGAT) (Alvarez et al , ; Hernández et al ., ; Amara et al ), a NADPH‐dependent glyceraldehyde‐3‐phosphate dehydrogenase (TadD) (MacEachran and Sinskey, ), a phosphatidic acid phosphatase type 2 enzyme (PAP2) (Hernández et al ., ), an ATP‐binding cassette transporter (Lpt1) (Villalba and Alvarez, ) and structural proteins involved in lipid body ontogeny (TadA) (MacEachran et al , ; Ding et al , ). Besides enzymes, transporters and structural proteins, the TAG‐accumulating machinery of rhodococci may include an unknown regulatory network probably integrated by global and specific regulatory proteins, which could coordinate the transition to a TAG‐producing phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, several genes/proteins and their contributions on TAG metabolism have been well described in R. opacus PD630 or R. jostii RHA1 used as models. Examples of these studies include proteins such as diacylglycerol acyltransferase enzymes (DGAT) (Alvarez et al , ; Hernández et al ., ; Amara et al ), a NADPH‐dependent glyceraldehyde‐3‐phosphate dehydrogenase (TadD) (MacEachran and Sinskey, ), a phosphatidic acid phosphatase type 2 enzyme (PAP2) (Hernández et al ., ), an ATP‐binding cassette transporter (Lpt1) (Villalba and Alvarez, ) and structural proteins involved in lipid body ontogeny (TadA) (MacEachran et al , ; Ding et al , ). Besides enzymes, transporters and structural proteins, the TAG‐accumulating machinery of rhodococci may include an unknown regulatory network probably integrated by global and specific regulatory proteins, which could coordinate the transition to a TAG‐producing phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in vitro specificity of a WS/DGAT enzyme from R. jostii RHA1 faced with diverse substrates was analysed (Barney et al, 2012). MacEachran & Sinskey (2013) identified an NADPH-dependent glyceraldehyde-3-phosphate dehydrogenase (TadD). This enzyme is activated during TAG accumulation in R. opacus PD630 and required for the generation of NADPH for fatty acid biosynthesis under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, NADPH and 3-phosphoglycerate can be then used for lipid synthesis. Interestingly, tadD overexpression in R. opacus PD630 resulted in an increase of TAG accumulation (28).…”
Section: Several Metabolic Reactions Provide Reducing Equivalents Formentioning
confidence: 97%
“…At the same time, NADPH, which is required for fatty acid biosynthesis, also inhibits glycogen synthesis, increasing intracellular availability of carbon for lipogenesis. In this context, MacEachran and Sinskey (28) reported that the ratio of NADPH to NADP ϩ is elevated in PD630 cultures grown under lipid production conditions compared to that in cultures grown under vegetative growth conditions. Finally, enzymes for glycogen degradation, such as glycogen phosphorylase, glycogen-debranching enzyme, and phosphoglucomutase, are induced under nitrogen-limiting conditions according to results of proteomic analysis (11).…”
Section: Biosynthetic Pathways In Competition With Lipogenesismentioning
confidence: 99%